2020
DOI: 10.1155/2020/2850780
|View full text |Cite
|
Sign up to set email alerts
|

Study on Restoration Materials for Historical Silty Earthen Sites Based on Lime and Starch Ether

Abstract: The relics built with soil are called earthen archaeological sites. Many silt earthen sites exposed to natural environment get seriously damaged and thus require urgent restoration with suitable materials. Previously, lime and glutinous rice slurry were used in the construction of earthen sites. However, lime is usually used in clay, and glutinous rice pulp is difficult to prepare and use on a large scale. Therefore, in this study, starch ether was selected to replace glutinous rice pulp. Lime and starch ether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…(1) Direct Shear Test Under Low Stress. e number of floors of rural buildings in the Yellow River region is low, and the actual vertical pressure is often lower than that of high-rise buildings [38]. In this paper, the vertical stress is 50 kPa, 100 kPa, 150 kPa, and 200 kPa, respectively.…”
Section: Mechanical Properties Of Improved Siltmentioning
confidence: 84%
“…(1) Direct Shear Test Under Low Stress. e number of floors of rural buildings in the Yellow River region is low, and the actual vertical pressure is often lower than that of high-rise buildings [38]. In this paper, the vertical stress is 50 kPa, 100 kPa, 150 kPa, and 200 kPa, respectively.…”
Section: Mechanical Properties Of Improved Siltmentioning
confidence: 84%
“…According to the principle of minimum intervention in the protection of cultural relics, traditional restoration materials should be used as far as possible. At present, the materials applied to the restoration of soil sites mainly include inorganic materials such as lime [3], cement [4], and hydraulic lime [5]. Lime is an air-hardening material whose mechanical properties are unstable in water environments, which leads to the adverse situation of repeated repair and destruction of soil sites [6].…”
Section: Introductionmentioning
confidence: 99%
“…Niu et al [ 10 ] improved the disintegration characteristics of soil sites in Northwestern China with a glutinous rice slurry, which provided a theoretical basis for the application of glutinous rice solution in the protection of soil sites. Kong et al [ 11 ] improved the shear strength and compressive strength of the site soil by adding lime and starch ether to the silt. Qian et al [ 12 ] conducted a study on the use of desulfurization waste to modify raw soil materials, and the results showed that the calcined desulfurization gypsum and the content of solid sulfur significantly improved the compressive strength of raw soil materials.…”
Section: Introductionmentioning
confidence: 99%